Identification and Screening of Novel Anti-Cancer Compounds for Aurora Kinase-A from Chemical Database - Singh, Ipsa A.; Lokhande, Kiran Bharat; Swamy, K. Venkateswara (Drug Research, 2022)
Aurora kinase is a group of enzymes that belongs to a serine-threonine family and plays a critical role in cellular division. Aurora Kinase A is overexpressed and distributed beyond the nucleus and is involved in tumorigenesis. Flavones are a class of flavonoids that are present in plants that show anticancer activity. Similar compounds of 2’Fluoroflavones are retrieved from the PubChem database. Then drug-like filters viz. REOS and PAINS were applied to remove toxic compounds using Canvas software, resulting in 3882 compounds being subjected to Glide docking with Aurora kinase A. The lead compounds were selected on the merit of hydrogen bonding, salt bridge, as well as pi-pi interactions, 4-(6-Fluoro-4-oxychromen-2yl) benzoic acid, has been found one of the best molecules from docking studies. The binding mode of the lead compound with AURKA reveals that the amino acid residues viz, Lys162, Ala213, and His280 are more important for binding with the binding affinity of -11.760 kcal/mol. The molecular dynamics simulations of 100 ns were done, which shows the mean RMSD value of 1.77 Å for all 3 complexes of the protein and Fluoroflavone and its analogs. This shows that Fluoroflavone and its 2 best analogs are tightly attached to the active sites and thus have conformational stability. Our finding suggests that 4-(6-fluoro-4-oxochromen-2-yl)benzoic acid and 4-(4-Oxochromen-2-yl)benzoate can be further used in vitro and in vivo experiments and can probably serve as a novel drug for cancer treatment.
Keywords: Aurora kinase A; Fluoroflavones; chemoinformatics; Glide docking; MD simulation; Enrichment calculations